The incidence of coxiella infection in Iraqi women with early pregnancy loss - Noor Alanbaki; Baydaa Hameed Abdullah; wassan Abdulkarreem Abbas; Mamdouh Mohamed Elbahnasawy (College of Pharmacy / Mustansiriyah University, 2024)
Query fever is a bacterial disease resulting from Coxiella burnetii (CB) infection in animals. It is well known that small ruminants who get Q fever lose their babies. People think pregnant women may also have lousy gestation results if they get the infection or the infection comes back to life during pregnancy. This study looks at how serologic results of Q fever and early pregnancy loss (EPL) are linked. In Baghdad, including Madinat Al-Imamain Al-Kadhmain Teaching Hospital and Abu Ghraib Hospital, multicenter case-control research was conducted from September to December 2022. A total of 90 women were enrolled in this investigation. Sixty clinically suffered from early pregnancy loss by having a nonviable intrauterine pregnancy. The other 30 women were subjects of comparable age, the week of pregnancy, and the healthy subjects as controls.  Using a commercial enzyme-linked immunosorbent assay (ELISA), serum samples were screened for antibodies against CB. Three (5%) cases tested positive for CB by ELISA. The study reveals no association between adverse gestation outcomes and positive Q fever serology. Age and abortion history were not significantly correlated with C. burnetii seropositivity, according to the findings of CB cases that tested positive results.